Mapping and analysing cultural ecosystem services in conflict areas - Santarém, Frederico; Saarinen, Jarkko; Brito, José Carlos (Ecological indicators, 2020)
•Mapping ecosystem services is crucial to reach the UN Sustainable Development Goals.•Large-scale analyses are vital to desert cultural ecosystem services mapping.•Constraints to cultural services need to be measured for ecosystem management.•Sahara-Sahel ecosystems are a perfect model to study cultural ecosystem services.•Deserts supply substantial cultural ecosystem services, threatened by global change. Human-mediated global environmental change threatens ecosystem services worldwide. Detailed cultural ecosystem services mapping is crucial to counteract ecosystem degradation, but such mapping exercises have been confined to small-scale analyses in developed countries. Additionally, disturbances constraining the supply of cultural ecosystem services transboundary have never been mapped, which hampers the accurate management of ecosystems, particularly in underdeveloped countries affected by human conflicts. The Sahara-Sahel ecoregions of Africa represent an excellent model to map the distribution of transboundary attractions and constraints to cultural ecosystem services due to the many conflicts affecting its drylands. We mapped and analysed the supply of cultural ecosystem services in the Sahara-Sahel, using a multicriteria approach that includes transboundary attractions and constraints playing at broader scales. We wanted to understand where are located the hotspots of cultural ecosystem services and which regions displaying the highest levels of attractions may be simultaneously threatened by constraint features. Overall, 35.4% of the study area displays high (27.9%) to very high (7.5%) levels of attractions to cultural ecosystem services supply, while 8.6% of the area displays high (7.5%) to very high (1.1%) levels of constraints that limit the usufruct of these services in the region. Our findings showed that the main mountains and wetlands of the region are supplying high levels of cultural ecosystem services but are threatened in some parts of their range by transboundary constraints. Some country-borders displayed a high concentration of constraints impacting desert biodiversity and human communities. This highlights the urgency of policymakers to reinforce transboundary strategic actions to halt the ongoing destruction of natural resources in the region. The developed approach is scalable and replicable in any ecosystem, including in those located in data-scarce regions. Including constraints to ecosystem services supply is paramount to achieve the United Nations Sustainable Development Goals.